2014
DOI: 10.1152/japplphysiol.01370.2013
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of the pulmonary chemoreflex following acute cervical spinal cord injury

Abstract: Bronchopulmonary C fibers are the primary chemosensitive afferents in the lung. The activation of bronchopulmonary C fibers evokes the pulmonary chemoreflex, which is characterized by apnea, hypotension, and bradycardia and is a critical reflex that modulates cardiorespiratory responses under physiological and pathological conditions. The present study was designed to investigate whether the pulmonary chemoreflex is altered following acute cervical spinal injury. A unilateral hemisection (Hx) or laminectomy (u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Spinal cord histology was conducted as previously described (34,52). The C2 spinal cord was cryoprotected and transversely sectioned into 40-m slices (CM 1850, Leica) and mounted on glass slides, stained with the cresyl violet (Acros Organics), and examined under a microscope (DM750, Leica).…”
Section: Spinal Cord Histologymentioning
confidence: 99%
See 1 more Smart Citation
“…Spinal cord histology was conducted as previously described (34,52). The C2 spinal cord was cryoprotected and transversely sectioned into 40-m slices (CM 1850, Leica) and mounted on glass slides, stained with the cresyl violet (Acros Organics), and examined under a microscope (DM750, Leica).…”
Section: Spinal Cord Histologymentioning
confidence: 99%
“…These results suggest that exogenous activation of the serotonergic system can specifically enhance the ipsilateral diaphragmatic motor outputs, but this approach may not be sufficient to improve respiratory functional recovery following chronic cervical spinal injury. cervical spinal cord injury; diaphragm; serotonin; respiration CERVICAL SPINAL CORD INJURY (SCI) usually interrupts bulbospinal pathways and results in respiratory dysfunction (33,35,52). Spinal hemisection at the second cervical spinal cord (i.e., C2Hx) is widely used to investigate respiratory function following cervical SCI in rodent models (16,19,21).…”
mentioning
confidence: 99%
“…The pulmonary chemoreflex is a critical defensive reflex evoked by activation of bronchopulmonary C-fibers. Our recent study (52) demonstrated that pulmonary chemoreflexes induced by intrajugular capsaicin injection was abolished 1 day post-C2Hx. However, it is unknown whether this effect is temporary or remains in the chronic injury phase.…”
mentioning
confidence: 90%
“…Although bronchopulmonary C‐fibre‐evoked pulmonary chemoreflexes have been extensively reported in many previous studies (Lin & Lee, ; Lee et al . ; Lee & Chang, ; Tsai & Lee, ; Lin et al . ), the influence of capsaicin‐induced bronchopulmonary C‐fibre activation on phrenic motoneuron bursting is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral phrenic nerves display identical inspiratory rhythmic activity under normal conditions; however, lateral cervical spinal cord injury usually interrupts the bulbospinal respiratory pathway and causes cessation of phrenic bursting or diaphragm EMG activity ipsilateral to the lesion (Zhou et al . ; Tsai & Lee, ; Hsu & Lee, ; Navarrete‐Opazo et al . ).…”
Section: Introductionmentioning
confidence: 99%